Radical Surgery and Reoperation in Supratentorial Malignant Glial Tumors - Daneyemez, M.; Gezen, F.; Çanakçi, Z.; Kahraman, S. (min - Minimally Invasive Neurosurgery, 1998)
The treatment modalities for gliomas are still questioning and searching. We reviewed the effect of the extent of surgical resection and reoperation on the length and quality of survival in 152 consecutive patients who underwent operation for supratentorial gliomas at GATA Neurosurgery clinic between 1985 to 1995.Seventy-two patients (50%) had glioblastoma multiforme (GBM), and 48 patients (33%) had anaplastic astrocytoma (AA). Gross total resection was achieved in 70 cases (49%), subtotal resection was performed in 60 cases (42%), and biopsy was carried out in 14 cases (9%). Thirty-two patients were reoperated for recurrency and the median interval between the first operation and reoperation was 9.5 months in glioblastoma multiforme, and 11.7 months in anaplastic astrocytoma. The resection groups were compared for age, sex, preoperative and postoperative Karnofsky rating, tumor location, postoperative radiation therapy, and chemotherapy, and survival according to multivariate analysis. Preoperative Karnofsky rating and surgical resection type were the most important factors related to survival after operation or reoperation. The gross total resection group lived longer than the subtotal resection group by life table analysis. Median survival of GBM was 76 weeks in gross total resection group, and 33 months in AA group with total resection (p < 0.001). Preoperative Karnofsky scores had a statistically significant effect on the quality of life and survival after operation and reoperation in all cases (p = 0.005). Radical surgery and reoperation also improve quality and length of life in selective malignant supratentorial gliomas.
Keywords: Glial tumor; Radical surgery; Reoperation; Survival